PENGARUH EXPERTISE KOMITE AUDIT DAN FRAUDULENT FINANCIAL STATEMENT TERHADAP AUDIT REPORT TIMELINESS DENGAN DIVERSITAS GENDER SEBAGAI VARIABEL MODERASI - Shinta Fitriani; Dian Saputra (Institut Bisnis dan Teknologi Pelita Indonesia, 2026)
This study aims to examine the influence of audit committee expertise and fraudulent financial statements on audit report timeliness, with gender diversity acting as a moderator, in property and real estate companies listed on the Indonesia Stock Exchange for the period 2023–2024. This study employs a quantitative approach using purposive sampling, resulting in 142 observations. Data analysis was conducted using multiple linear regression with a Moderated Regression Analysis (MRA) approach. The results indicate that audit committee expertise has a positive and significant effect on audit report timeliness, whilst fraudulent financial statements do not show a significant effect. Furthermore, gender diversity was found to weaken the effect of audit committee expertise on audit report timeliness, but did not play a role in moderating the relationship between fraudulent financial statements and audit report timeliness. These findings indicate that audit committee expertise is a key factor in improving the timeliness of audit reporting, whilst the effectiveness of gender diversity depends on the context of the relationships between the variables tested.